2015
DOI: 10.1371/journal.pone.0116485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny and Biogeographic Diversification of Linnaeoideae (Caprifoliaceae s. l.) Disjunctly Distributed in Eurasia, North America and Mexico

Abstract: Linnaeoideae is a small subfamily of erect or creeping shrubs to small trees in Caprifoliaceae that exhibits a wide disjunct distribution in Eurasia, North America and Mexico. Most taxa of the subfamily occur in eastern Asia and Mexico but the monospecific genus Linnaea has a circumboreal to north temperate distribution. In this study, we conducted phylogenetic and biogeographic analyses for Linnaeoideae and its close relatives based on sequences of the nuclear ribosomal ITS and nine plastid (rbcL, trnS-G, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 73 publications
7
73
0
1
Order By: Relevance
“…Actually, relationships among Symphoricarpos , Triosteum and Leycesteria varied in earlier studies. Some studies showed that Symphoricarpos and Leycesteria formed a sister group (Pyck & Smets, ; Smith, ; Jacobs et al, ), others showed that Symphoricarpos grouped with Triosteum (Bell, ; Beaulieu & Donoghue, ; Wang et al, ). Thus, perhaps it is not strange that two Symphoricarpos species grouped with Leycesteria and Triosteum , respectively, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, relationships among Symphoricarpos , Triosteum and Leycesteria varied in earlier studies. Some studies showed that Symphoricarpos and Leycesteria formed a sister group (Pyck & Smets, ; Smith, ; Jacobs et al, ), others showed that Symphoricarpos grouped with Triosteum (Bell, ; Beaulieu & Donoghue, ; Wang et al, ). Thus, perhaps it is not strange that two Symphoricarpos species grouped with Leycesteria and Triosteum , respectively, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…(Wang et al, 2015). One of the most parsimonious trees from an analysis of plastid data (rbcL,matK,ndhA,.…”
Section: Nectary Ultrastructurementioning
confidence: 99%
“…Phylogenetics based on molecular markers have redefined circumscriptions in Linnaeeae (Landrein et al, 2012;Wang et al, 2015), and it is also important to characterize these new groups morphologically (Endress & Matthews, 2012).…”
Section: Nectary Morphologymentioning
confidence: 99%
See 2 more Smart Citations